Rise in Oil Price and Economic Growth in Pacific Island An Empirical Study - Jayaraman, T.K; Lau, Evan (School Of Economics University Of The South Pacific, 2008)
None of the 14 Pacific Island countries (PICs), except Papua New Guinea has any fossil fuel resources. Consequently, all the 13 PICs are totally dependent on oil imports for their economic activities. Recent surges in oil prices have had serious economic repercussions on economic growth. This paper applies panel analysis procedures to five major PICs, namely Fiji, Samoa, Solomon islands, Tonga and Vanuatu with a view to assessing the impact of oil price on economic growth. The findings are that oil price, economic growth and international reserve are cointegrated. The study findings are that although in the long run there is no long run causality relationship between these variables, in the short run the causality linkage runs from oil prices and international reserve to economic growth. The paper concludes with a brief discussion on policy options.